Acylated Ghrelin Supports the Ovarian Transcriptome and Follicles in the Mouse: Implications for Fertility - Sominsky, Luba; Goularte, Jeferson F.; Andrews, Zane B.; Spencer, Sarah J. (Frontiers in Endocrinology, 2019)
Ghrelin, an orexigenic gut-derived peptide, is gaining increasing attention due to its multifaceted role in a number of physiological functions, including reproduction. Ghrelin exists in circulation primarily as des-acylated and acylated ghrelin. Des-acyl ghrelin, until recently considered to be an inactive form of ghrelin, is now known to have independent physiological functionality. However, the relative contribution of acyl and des-acyl ghrelin to reproductive development and function is currently unknown. Here we used ghrelin-O-acyltransferase (GOAT) knockout (KO) mice that have no measurable levels of endogenous acyl ghrelin and chronically high levels of des-acyl ghrelin, to characterise how the developmental and life-long absence of acyl ghrelin affects ovarian development and reproductive capacity. We combined the assessment of markers of reproductive maturity and the capacity to breed with measures of ovarian morphometry, as well as with ovarian RNA sequencing analysis. Our data show that while GOAT KO mice retain the capacity to breed in young adulthood, there is a diminished number of ovarian follicles (per mm3) in the juvenile and adult ovaries, due to a significant reduction in the number of small follicles, particularly the primordial follicles. We also show pronounced specific changes in the ovarian transcriptome in the juvenile GOAT KO ovary, indicative of a potential for premature ovarian development. Collectively, these findings indicate that an absence of acyl ghrelin does not prevent reproductive success but that appropriate levels of acyl and des-acyl ghrelin may be necessary for optimal ovarian maturation.